Characterization of drug–drug interactions on the pharmacokinetic disposition of busulfan in paediatric patients during haematopoietic stem cell transplantation conditioning. Issue 5 (20th December 2021) - Dunn, Allison; Moffett, Brady S.; Ivaturi, Vijay; Gobburu, Jogarao V. S.
Abstract : Aim: The study objective was to develop a population pharmacokinetic model for busulfan to comprehensively examine drug–drug interactions in paediatric patients undergoing haematopoietic stem cell transplantation. Currently, there is limited evidence to substantiate potential drug–drug interactions with busulfan. Methods: This retrospective study population was comprised of 250 patients receiving, on average, 0.8 mg/kg intravenous busulfan as pretreatment. All model analyses were conducted using nonlinear mixed effects modelling in Pumas v2.0. The metabolic pathways of primary interest were glutathione conjugation and cytochrome P450 (CYP) activity. Concomitant medications were categorized as CYP inhibitors, inducers or glutathione S‐transferase depleters, and included in the model as conditional covariates. A bootstrap simulation and visual predictive check were conducted to qualify the final model. Results: The final 1‐compartment model incorporates covariates of weight and age in relation to their effects on both total body clearance and volume of distribution. The estimated typical values of clearance and volume were 1.138 L/h (CI: 1.095–1.179 L/h) and 3.527 L (CI: 3.418–3.621 L), respectively. No significant changes in clearance were observed when medications that alter proposed hepatic and metabolic pathways of busulfan were coadministered. Conclusion: To the best of our knowledge, this is the largest single centre study of busulfan in children and the first to quantify the maturation effect of both clearance and volume. This study could not demonstrate a difference in busulfan clearance when comparing patients who received medications that alter the glutathione S‐transferase, CYP3A4 or CYP2C9 pathway to those who did not.